Fabrication of a lead-free ternary ceramic system for high energy storage applications in dielectric capacitors - Khan, Azam; Gul, Noor Shad; Luo, Mao; Wu, Jianbo; Khan, Shahan Zeb; Manan, Abdul; Wang, Xiu-Jian; Khan, Taj Malook (Frontiers in Chemistry, 2022)
The importance of electroceramics is well-recognized in applications of high energy storage density of dielectric ceramic capacitors. Despite the excellent properties, lead-free alternatives are highly desirous owing to their environmental friendliness for energy storage applications. Herein, we provide a facile synthesis of lead-free ferroelectric ceramic perovskite material demonstrating enhanced energy storage density. The ceramic material with a series of composition (1-z) (0.94Na0.5Bi0.5TiO3-0.06BaTiO3)-zNd0.33NbO3, denoted as NBT-BT-zNN, where, z = 0.00, 0.02, 0.04, 0.06, and 0.08 are synthesized by the conventional solid-state mix oxide route. Microphases, microstructures, and energy storage characteristics of the as-synthesized ceramic compositions were determined by advanced ceramic techniques. Powder X-ray diffraction analysis reveals pure single perovskite phases for z = 0 and 0.02, and secondary phases of Bi2Ti2O7 appeared for z = 0.04 and 0.08. Furthermore, scanning electron microscopy analysis demonstrates packed-shaped microstructures with a reduced grain size for these ceramic compositions. The coercive field (Ec) and remnant polarization (Pr) deduced from polarization vs. electric field hysteresis loops determined using an LCR meter demonstrate decreasing trends with the increasing z content for each composition. Consequently, the maximum energy storage density of 3.2 J/cm3, the recoverable stored energy of 2.01 J/cm3, and the efficiency of 62.5% were obtained for the z content of 2 mol% at an applied electric field of 250 kV/cm. This work demonstrates important development in ceramic perovskite for high power energy storage density and efficiency in dielectric capacitors in high-temperature environments. The aforementioned method makes it feasible to modify a binary ceramic composition into a ternary system with highly enhanced energy storage characteristics by incorporating rare earth metals with transition metal oxides in appropriate proportions.